Tandem Regioselective Rhodium-Catalyzed Hydroformylation–Enantioselective Aminocatalytic anti-Mannich Reaction - Diezel, Sonja; Breit, Bernhard (Synthesis, 2014)
The first tandem regioselective hydroformylation and enantioselective organocatalytic anti-Mannich reaction is reported. Starting from α-olefins, valuable functionalized amino acid derivatives were obtained in excellent yields and with high levels of diastereo- and enantioselectivities. The products represent valuable building blocks for biologically and pharmaceutically interesting targets.
Keywords: tandem reactions; asymmetric synthesis; homogeneous catalysis; organocatalysis; hydroformylation